PENGARUH ANEMIA DAN STATUS GIZI TERHADAP KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD Dr. M. YUNUS BENGKULU TAHUN 2016 - Erna Lestari (Jurnal Kesehatan STIKes IMC Bintaro, 2018)
Background : Hypertension is one of the non-communicable diseases (NCDs) are referred to as the silent killer with symptoms can vary on each individual and is similar to the symptoms of other diseases. Hypertension is a condition that is often found in health care. Hypertension is one of the biggest risk factor causes of morbidity and mortality of cardiovascular disease. One of the causes of hypertension are lifestyle factors such as nutrition, alcohol consumption and smoking, physical activity, obesity, and psychological stress can increase blood pressure. Objective : The purpose of this study was to determine the relationship of lifestyle with blood pressure in hypertensive patients at the Saruni Hafiah Clinic, Pandeglang Banten. Method : The study design was descriptive analytic cross sectional nonexperimental quantitative approach. Subjects were 55 patients with hypertension in Saruni Hafiah Clinic, Pandeglang Banten. Respondents were measured blood pressure, weight, height and fill out a questionnaire lifestyle and General Health Questionnaire-12 (GHQ-12). Result : The results showed significant relationship between lifestyle with blood pressure in hypertensive patients at the Saruni Hafiah Clinic, Pandeglang Banten (pvalue ≤ 0.05). Significant relationship was also found on lifestyle factors alcohol consumption with the blood pressure of patients with hypertension (pvalue ≤ 0.05). However there was no significant relationship between nutrition, tobacco consumption, physical activity, psychological stress, and obesity with blood pressure in hypertensive patients at the Saruni Hafiah Clinic, Pandeglang Banten (pvalue > 0.05).